PENGARUH KUALITAS LAYANAN, PERCEIVED RISK TERHADAP KEPUASAN PENGGUNA DAN MINAT MEMBELI KEMBALI PADA TOKO ONLINE BUKALAPAK.COM - Syaripudin Bahar; Rizali Hadi; Agus Febrianto (Universitas Lambung Mangkurat, 2020)
Syaripudin Bahar, D2A215010, 2019, Effect of service quality, perceived risk to user satisfaction and interest in buying back the online store Bukalapak.com (study at FKIP ULM student Banjarmasin Bukalapak.com users online site). Supervised by: Rizali Hadi and Agus Pebrianto.The purpose of this study was to examine and analyze the impact of service quality, perceived risk to user satisfaction and interest in buying back the Bukalapak.com online store. This type of research is explanatory research. Population and sample in this research is Bukalapak.com site users with a sample of 382 students and sampling techniques with proportionate stratified random sampling technique. The method used is Structural Equation Model (SEM). Four (4) The variables used in this study is the variable quality of service, perceived risk variables, user satisfaction variables and variable interest in buying back the five (5) hypothesis. The results showed that (H1) quality of service no significant effect on user satisfaction, (H2) Dimensions of service quality did not significantly affect the interest repurchase, (H3) Perceived risk significant effect on user satisfaction, (H4) Perceived risk has no significant effect on the interest repurchase, and (H5) user satisfaction significantly influence buying interest back on Bukalapak.com site. Two (2) a significant hypothesis is H3 and H5, while three (3) significant hypotheses are H1, H2 and H4.Keywords: quality of service, perceived risk,user satisfaction.